Antibacterial Activity Test of Etanol Extract of Black Sea Cucumber (Holothuria atra) against the Bacteria Staphylococcus aureus and Escherichia coli - Fadli Husain; Tegar Abdiyanto Padja; Nangsih Sulastri Slamet; Moh. Usman Nur; Fitriah Ayu Magfirah Yunus; Fadlun Abubakar; Febriyanti Polontalo (JURNAL INFO KESEHATAN, 2025)
Black Sea cucumber (Holothuria atra) contain chemical compounds that has antibacterial activity. One of the bacteria that is pathogenic to humans and at risk of death are Staphylococcus aureus and Eschericia coli. The purpose of this study is to ascertain whether black sea cucumber ethanol extract in Pataomeme waters has antibacterial activity against the microorganisms E. coli and S. aureus. The type of research used is quantitative research with quasi laboratory experiments. Antibacterial activity test using disc diffusion method. Black Sea cucumber extract was made in 3 concentrations, consisted of 7.5%, 10% and 12.5%. The results showed that black sea cucumber extract has antibacterial activity seen through the inhibition zone formed. The maximum inhibition zone is at a concentration of 12.5% sea cucumber extract, which is 28.59 mm against S. aureus bacteria and 21.02 mm against E. coli bacteria. According to our results, sea cucumber may be a suitable marine source of antibacterial substances. To ascertain its potential use in other areas of medicine, more in vivo research must be conducted.